1995
DOI: 10.1113/jphysiol.1995.sp020991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subsarcolemmal and bulk calcium concentration during spontaneous calcium release in rat ventricular myocytes.

Abstract: 1. The aim of these experiments was to compare the time course of changes in intracellular Ca2+ concentration ([Ca2+]i) measured in the bulk cytoplasm with those estimated to occur near the sarcolemma. Sarcolemmal Na(+)-Ca2+ exchange current and [Ca2+]i were measured in single, voltage-clamped ventricular myocytes. 2. Spontaneous Ca2+ release from the sarcoplasmic reticulum (SR) resulted in a transient inward current. This current developed and decayed more quickly than the accompanying changes in [Ca2+]i (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 28 publications
11
91
0
Order By: Relevance
“…Figure 9 shows a simultaneously recorded Ca¥ transient and inward current, both recorded with a 10 Hz low-pass filter. Note that the caffeine-induced inward current precedes the [Ca¥]é by about 100 ms as noted previously in other cell types (Callewaert et al 1989;Trafford, Diaz, O'Neill & Eisner, 1995). Callewaert et al (1989) suggested that the lag was caused by the slow kinetics of indo_1; however the delays due to indo_1 are only of the order of 5-10 ms (Westerblad & Allen, 1996) and we think it more likely that the delay is because the inward current is triggered by the rise of [Ca¥]é close to the surface membrane whereas it takes some time for caffeine to diffuse to the interior of the cell and trigger Ca¥ release there (Trafford et al 1995).…”
Section: Identity Of the Caffeine-induced Inward Currentsupporting
confidence: 58%
“…Figure 9 shows a simultaneously recorded Ca¥ transient and inward current, both recorded with a 10 Hz low-pass filter. Note that the caffeine-induced inward current precedes the [Ca¥]é by about 100 ms as noted previously in other cell types (Callewaert et al 1989;Trafford, Diaz, O'Neill & Eisner, 1995). Callewaert et al (1989) suggested that the lag was caused by the slow kinetics of indo_1; however the delays due to indo_1 are only of the order of 5-10 ms (Westerblad & Allen, 1996) and we think it more likely that the delay is because the inward current is triggered by the rise of [Ca¥]é close to the surface membrane whereas it takes some time for caffeine to diffuse to the interior of the cell and trigger Ca¥ release there (Trafford et al 1995).…”
Section: Identity Of the Caffeine-induced Inward Currentsupporting
confidence: 58%
“…In cardiac myocytes, NCX is mostly located in the TT (6,10) and is preferentially modulated by Ca 2ϩ released from the SR, as indicated by functional measurements (23,26). We found that NKA-␣2 function is concentrated in the TT vs. external sarcolemma, with the amount of NKA-␣1 and NKA-␣2 in the TT being comparable.…”
Section: Discussionmentioning
confidence: 57%
“…Actual Ca 2ϩ transient from control was used 19 ; for HF, the peak was reduced by 30%. 4 ] i , 23 we approximated [Ca 2ϩ ] sm by using the procedure described by Weber et al 24 (Figure 5B ] sm may be elevated transiently as the result of Na ϩ influx through Na ϩ channels or NCX, favoring more outward I NCX .…”
Section: Discussionmentioning
confidence: 99%